Argentina - COVID-19 High Frequency Phone Survey - World Bank (Washington, DC: World Bank, 2022)
The share on employed population in June 2021was similar to the pre-pandemic levels (Feb 2020). However, 13.5 percent of those who had a job before the pandemic started, have lost their job by June 2021.Women and low skilled workers were the most affected. Food insecurity has doubled when compared with pre pandemic levels and has not improved with respect to May 2020. School-age children were mainly attending virtual classes, but 5 percent were not attending presential or virtual classes. Household chores increased disproportionally for women. The increase on time spent in education and schoolwork help to children is the highest of the region. Reported mental health impacts are among the highest in the region, particularly for women.